Bem-vindas de volta : a autodefinição no cinema de Tila Chitunda, Ana Pi, Safira Moreira e Yasmin Thayná - Nicole Faria Batista (2021)
Based on the presentation of the artistic trajectory of Tila Chitunda, Ana Pi, Safira Moreira and Yasmin Thayná, four brazilian black women filmmakers, as well as the context of the field in which his cinema is inserted, this thesis seeks to demonstrate how their films invoke a cinematographic self-definition, analyzing them alongside the concept as it was written by Patricia Hill Collins (2019). The comparative analysis of the short movies Nome de Batismo - Alice (2017), by Tila Chitunda; NoirBlue (2018), by Ana Pi ; Travessia (2020) by Safira Moreira and Fartura (2019), by Yasmin Thayná shows how - each in its own way - they elaborate personal and familiar stories, reconnecting them to the collective history of black people.